2018
DOI: 10.1371/journal.pone.0200488
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of SPECT/CT imaging in colorectal liver metastases response after 90Y-radioembolization

Abstract: The aim of this study was to evaluate a modified method of calculating the 99mTc/90Y tumor-to-normal-liver uptake ratio (mT/N) based on SPECT/CT imaging, for use in predicting the overall response of colorectal liver tumors after radioembolization. A modified phantom-based method of tumor-to-normal-liver ratio calculation was proposed and assessed. In contrast to the traditional method based on data gathered from the whole tumor, gamma counts are collected only from a 2D region of interest delineated in the SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have shown the feasibility and value of quantitative SPECT for the evaluation of the extra-and intrahepatic distribution of 90 Y and absorbed dose quantifications after TARE (19). More recently, several studies investigating hepatic metastases found CT perfusion imaging and metabolic response assessment using PET predictive of tumor response early after TARE (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the feasibility and value of quantitative SPECT for the evaluation of the extra-and intrahepatic distribution of 90 Y and absorbed dose quantifications after TARE (19). More recently, several studies investigating hepatic metastases found CT perfusion imaging and metabolic response assessment using PET predictive of tumor response early after TARE (20).…”
Section: Discussionmentioning
confidence: 99%
“…One study noted a strong statistically significant dose-effect of resin Y90 microspheres with improved hepatic tumor PFS and OS, with mean tumor dose of 51 Gy (± 28 Gy), range 7–174 Gy (15). In a prospective study of 21 mCRC patients receiving resin Y90 SIRT employing SPECT/CT for post-SIRT dosimetry, the tumor/normal ratio of absorbed dose was significantly ( p < 0.001) associated with radiographic response (RECIST 1.1), longer PFS and OS in those patients with a T/N ratio of at least 1.7 or tumor dose of 70 Gy (14). Our patients generally received a lower mean tumor dose of Y90 than these studies which might be a factor in the comparatively lower response rate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the absorbed dose D in each whole sector region, i.e. including rods and plastic, is given by the relation ( 6 ):…”
Section: Methodsmentioning
confidence: 99%